Cognitive Capital and Islands of Innovation: The Lucas Growth Model from a Regional Perspective - Andrea Caragliu; Peter Nijkamp (Tinbergen Institute, 2011)
Knowledge triggers regional growth. Evidence suggests that skilled labour force concentrates in islands of innovation, determining an advantage for innovative regions and a challenge for lagging ones. We address the role of knowledge in shaping effective markets for skilled labour. Estimates are based on the Lucas (1988) model, with EVS and EUROSTAT data. The externality driving growth in the model is cognitive capital. Empirical tests show that a higher endowment of cognitive capital generates increasing returns to knowledge, favouring the emergence of islands of innovation; regions with a high endowment of cognitive capital attract knowledge spillovers from neighbours.
urn:NBN:nl:ui:31-1871/38517
Keywords: C21; E24; R11; 330; human capital; cognitive capital; knowledge spillovers; islands of innovation; Humankapital; Kognition; Wissenstransfer; Innovation; Regionales Wachstum; Neue klassische Makroökonomik; Schätzung; EU-Staaten